La vulnérabilité de l’approvisionnement en eau dans l’agglomération pacénienne : le cas du sous-système El Alto - Sébastien Hardy (Cybergeo, 2009)
Vulnerability in an urban background is generally considered through population indicators, such as the level of poverty, the level of education, etc. Nonetheless, these represent but one aspect of urban vulnerability. Seeking to evaluate the vulnerability of elements considered essential to the operating of the city allows us to complete the approach and to reveal other facets of vulnerability that are frequently overlooked. By looking at the vulnerability of water provision in the agglomeration of La Paz, the analysis emphasises the weaknesses of this element that is essential to urban functioning. It also points out how this vulnerability can be transmitted to other essential elements which need water to operate (health centres, inhabitants, etc.) and so can provoke crises. The analysis of vulnerability makes it possible to highlight the points of the system provision that must be improved in a perspective of preventative planning.